Prevalencia de parásitos gastrointestinales en caninos domésticos (canis lupus familiaris), en el distrito metropolitano de Quito parroquia de Pintag barrio el Rosario. - Catagña Males, Raquel Cristina (2020)
This research was carried out in the Rosario neighborhood of the Parish of Pintag of the Metropolitan District of Quito, based on determining the prevalence of gastrointestinal parasites in domestic canines (canis lupus familiaris), through coproparasitic analysis, to structure disease prevention measures Zoonotic parasitic The technique that was put into practice was that of sheather, the total number of animals sampled were 103 obtaining the following results: animals positive to parasites 66 representing 64.07% and 37 animals were negative interpreting as 35.95%. According to the type of parasite found first, Ancylostoma caninum with 42.71%, followed by Toxocara Canis reflecting 13.6%, Dipylidium caninum with 3.89%, Trichuris vulpis with 4.85%, finally Tenia with 0.97%. Canines between 0-12 months, of them 26 positive animals representing 25.2%; Animals 1-5 years is reflected 38 positive with 36.8%; Animals older than 5 years of them 8 positive animals with 7.76%. In the sex variable of the canines, 48 positive cases were observed for males, 32 cases of Ancylostoma caninum, which represents 31.06%, 11 positive for Toxocara canis with 10.67%, 4 positive for Dipylidium caninum, which represents 3 , 88% and 1 positive for Tenia with 0.97%. In females, parasitic positive were 11 patients with Ancylostoma giving 10.66%, 4 positive for Toxocara canis with 3.88% and 5 positive animals for Trichuris vulpis representing 4.85%. Variable small race found 8 positive in the case of Ancylostoma caninum with 7.76%, 4 positive for Toxocara canis representing 3.88%. For the medium race, 24 positive cases for Ancylostoma caninum which is 23.30%; 3 positive to Toxocara canis with 2.91%; 2 positive cases for Trichuris vulpis. For the large race, 21 positive cases for Ancylostoma representing 20.38%; 2 positive for Toxocara canis with 1.97%; 4 positive cases for Dipylidium caninum with 3.88%; 1 positive for Tenia with 0.97% It is necessary to implement health education actions to the community and the development of deworming plans for pets